2012
DOI: 10.2967/jnumed.111.088518
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Dosimetry Studies for 18F-NOS as a Potential PET Radiopharmaceutical for Inducible Nitric Oxide Synthase in Humans

Abstract: Nitric oxide (NO), the end product of the inducible form of NO synthase (iNOS), is an important mediator of a variety of inflammatory diseases. Therefore, a radiolabeled iNOS radiopharmaceutical for assessing iNOS protein concentration as a marker for its activity would be of value to the study and treatment of NO-related diseases. We recently synthesized an 18 F-radiolabeled analog of the reversible NOS inhibitor, 2-amino-4-methylpyridine ( 18 F-NOS), and confirmed its utility in a murine model of lung inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Organ residence times and estimates of best-and worse-case scenarios were calculated from the percentage injected dose per organ derived from the human images and entered into the OLINDA/ EXM software program (version 1.1; Vanderbilt University, Nashville, Tenn) to estimate individual organ doses and whole-body effective doses (24). Given the small number of subjects for the human dosimetry study, statistical analysis was not performed on the human image data.…”
Section: Human Dosimetry Estimatesmentioning
confidence: 99%
“…Organ residence times and estimates of best-and worse-case scenarios were calculated from the percentage injected dose per organ derived from the human images and entered into the OLINDA/ EXM software program (version 1.1; Vanderbilt University, Nashville, Tenn) to estimate individual organ doses and whole-body effective doses (24). Given the small number of subjects for the human dosimetry study, statistical analysis was not performed on the human image data.…”
Section: Human Dosimetry Estimatesmentioning
confidence: 99%
“…This tracer may also still provide useful information about iNOS expression in clinical trials in which a baseline scan can be obtained before an antiinflammatory therapy is initiated. Nevertheless, 1 previously published study investigating 18 F-NOS in transplanted heart grafts demonstrated a small increase in signal, suggesting that further chemical modifications may be needed to improve in vivo binding (23). Such tracers could potentially image a wider range of in vivo iNOS expression in the lungs as well as other organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry testing was repeated after endotoxin administration. 18 F-NOS was synthesized as previously described (23). Vital sign monitoring was performed throughout the study as previously reported (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO є важливим і унікальним медіатором багатьох фізіологічних функцій та патологічних процесів. NO генерується у разі окиснення L-аргініну до L-цитруліну ензимами родини синтаз оксиду азоту (NO-синтаза, NOS; L-аргінін, NADPH: кисень оксидоредуктаза; [EC 1.14.13.39]) [14]. За фізіологічних умов пул NO у судинах забезпечується функціонуванням ендотеліальної ізоформи NOS (eNOS).…”
Section: результати досліджень і їхнє обговоренняunclassified